Attenuation analysis and acoustic pressure levels for double expansion chamber reactive muffler: Part 2. (June 2018) - Kulkarni, Mahesh V; Ingle, Ravindra B
The major source responsible for noise pollution is internal combustion engine. These engines are used for various purposes such as in automobiles, locomotives, and in various manufacturing machineries. In an engine, the exhaust noise and the noise produced due to friction of various parts of the engine share maximum contribution to noise pollution. Muffler is a device used to reduce noise within the exhaust system. It is arranged along the exhaust pipe for the purpose of noise attenuation. The paper describes the propagation of pressure wave in a double expansion chamber reactive muffler. The approach is useful in analysis of damping for propagation of harmonic pressure waves. The purpose of paper is to describe the finite element analysis of double expansion chamber reactive muffler using pressure acoustics and to validate it with experimental evaluation using two-load method.